Atomic packing in Fe-based metallic glasses. (1st January 2016) - Yu, Q.; Wang, X.D.; Lou, H.B.; Cao, Q.P.; Jiang, J.Z.
Abstract: Atomic packing of three Fe-based metallic glasses (MGs) has been studied by X-ray diffraction and X-ray absorption fine structure, combining with reverse Monte Carlo (RMC) and ab initio molecular dynamics (AIMD) simulations. It is found that the addition of Y and Nb atoms to the binary Fe–B MG mainly stabilizes large high-coordinated polyhedra by substituting the center Fe atoms, promoting the formation of icosahedron-like clusters and their connectivity with high-coordinated polyhedra. Moreover, the heterogeneities in local structures are found to increase due to element segregations of Fe, Y and Nb atoms. The obtained results indicate that the large-sized Y and Nb atoms can frustrate the geometry of competing crystalline phases and improve the atomic packing efficiency, therefore leading to the enhanced glass forming ability. Graphical abstract: